Penyuluhan Penggunaan Lampu Navigasi Pada Kapal Nelayan Desa Wawontulap Untuk Menghindari Bahaya Tubrukan di Laut: Socialization on the Use of Navigation Lights for the Coastal Fisherman Society of Wawontulap Village to Avoid Collision Hazard at Sea - Silalahi, Aliong; Irawan, Santun; Frastika, Yustiani (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2023)
Risks of transportation safety are still a common issue in Indonesia. Communities living in coastal and marine areas, the majority of whom work as fishermen, still rely on traditional knowledge and skills. Wawontulap Village is located in the Tatapaan District with a total of 80 active fishermen, most of whom use small-scale traditional fishing boats with 50 cc to 80 cc motor engines and without adequate navigation tools, thus impacting visibility for ship maneuvers. fisherman. The position and potential for catching larger fish at night is a challenge for the fishing community in Wawontulap Village. This is because at night many fishing or fishing boats with larger sizes also descend into the sea which can cause a collision hazard between ships. The problem of navigation tools in the form of navigation lights is deemed necessary to find a solution immediately. Navigation lights on board apart from functioning as navigation guides can also be used as lighting and communication tools in the form of light signals if fishermen need help at any time. the method of socialization and delivery of assistance in the form of 3 (three) navigation lights which were handed over symbolically to village officials (the old law). From this community service activity it shows that fishermen's knowledge of the importance of navigation lights becomes clear and the danger of ship collisions when fishermen go outside to catch fish can be avoided.